2010
DOI: 10.1186/1471-2393-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Costs of vaginal delivery and Caesarean section at a tertiary level public hospital in Islamabad, Pakistan

Abstract: BackgroundPublic hospitals in developing countries, rather than the preventive and primary healthcare sectors, are the major consumers of healthcare resources. Imbalances in rational, equitable and efficient allocation of scarce resources lie in the scarcity of research & information on economic aspects of health care. The objective of this study was to determine the average cost of a spontaneous vaginal delivery and Caesarean section in a tertiary level government hospital in Islamabad, Pakistan and to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 13 publications
7
73
5
1
Order By: Relevance
“…A similar observation was reported in previous studies [7,18]. Also, the duration of hospital stay added significantly to expenditure.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A similar observation was reported in previous studies [7,18]. Also, the duration of hospital stay added significantly to expenditure.…”
Section: Discussionsupporting
confidence: 76%
“…Women who had an abdominal delivery spent significantly more than women with vaginal delivery. Previous studies also reported similar findings, where clients were observed to have spent significantly higher for deliveries via caesarean section as against vaginal deliveries [5][6][7]. Women who had surgery necessarily had to pay anaesthesia and theatre fees while those who had vaginal delivery paid only a flat delivery fee.…”
Section: Discussionsupporting
confidence: 67%
“…10 Cost can be a major issue in seeking alternate maternity health care. 11 Another study done in Pakistan showed that low literacy rate of mothers and low socioeconomic status may contribute to poor utilization of primary health care services. 12 This study showed that literacy rate was 30.7% among mothers which is in line with literacy rate of women in rural areas of Pakistan i.e., 25%.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study of 133 post-partum women living in Islamabad, Pakistan estimated the average monthly household income for families was equivalent to $149 USD (10,000 rupees at the time of publication) and the average cost of C-section was equivalent to $161 USD (10,868 rupees) compared to vaginal delivery cost of $79 USD (5,278 upees) (Khan & Zaman, 2010). In another study of 438 women living in Kathmandu, the willingness of women to pay for a C-section ($157 for normal vaginal delivery and $171 for C-section pre-delivery and $71 for NVD and $236 for CS post-delivery) compared with a vaginal delivery was studied pre and post birth, with resulting increase in reports of…”
Section: Cost Comparisons By Birth Modementioning
confidence: 99%